COMPETITION AND GENDER PREJUDICE: ARE DISCRIMINATORY EMPLOYERS DOOMED TO FAIL?. Issue 2 (22nd January 2014) - Weber, Andrea; Zulehner, Christine
Abstract According to Becker's famous theory on discrimination (Gary Becker, 1957, The Economics of Discrimination, University of Chicago Press), entrepreneurs with a strong prejudice against female workers forgo profits by submitting to their tastes. In a competitive market their firms lack efficiency and are therefore forced to leave. We present new empirical evidence for this prediction by studying the survival of start‐up firms in longitudinal matched employer–employee data. We find that firms with strong preferences for discrimination approximated by a low share of female employees relative to the industry average have significantly shorter survival rates. This is especially relevant for firms starting out with female shares in the lower tail of the distribution. Competition at the industry level additionally reduces firm survival and accelerates the rate at which prejudiced firms are weeded out. We also find evidence for employer learning as highly discriminatory start‐up firms that manage to survive submit to market powers and increase their female workforce over time.